Capacity building dan pendidikan keluarga / Rr. Leslie Retno Angeningsih, Nuraini Dwi Astuti, Rini Dorojati - LESLIE RETNO ANGENINGSIH , RR.; NURAINI Dwi Astuti; RINI DOROJATI (Deepublish, 2013)
xviii, 137 hlm. : ilus. ; 23 cm.